Histomorhological and clinical evaluation of maxillary alveolar ridge reconstruction after craniofacial trauma by applying combination of allogeneic and autogenous bone graft - Francesco Saverio De Ponte; Roberto Falzea; Michele Runci; Enrico Nastro Siniscalchi; Floriana Lauritano; Ennio Bramanti; Gabriele Cervino; Marco Cicciu (Chinese Journal of Traumatology, 2017)
A variety of techniques and materials for the rehabilitation and reconstruction of traumatized maxillary ridges prior to dental implants placement have been described in literature. Autogenous bone grafting is considered ideal by many researchers and it still remains the most predictable and documented method. The aim of this report is to underline the effectiveness of using allogeneic bone graft for managing maxillofacial trauma. A case of a 30-year-old male with severely atrophic maxillary ridge as a consequence of complex craniofacial injury is presented here. Augmentation procedure in two stages was performed using allogeneic and autogenous bone grafts in different areas of the osseous defect. Four months after grafting, during the implants placement surgery, samples of both sectors were withdrawn and submitted to histological evaluation. On the examination of the specimens, treated by hematoxylin and eosin staining, the morphology of integrated allogeneic bone grafts was revealed to be similar to the autologous bone. Our clinical experience shows how the allogeneic bone graft presented normal bone tissue architecture and is highly vascularized, and it can be used for reconstruction of severe trauma of the maxilla.